Natural-Series Radionuclides in Traditional Aboriginal Foods in Tropical Northern Australia: A Review. (2004) - Martin, Paul; Ryan, Bruce
Abstract : This paper gives a review of available information on natural-series radionuclides in traditional Aboriginal foods of northern Australia. Research on this topic has been carried out primarily for radiological impact assessment purposes in relation to uranium mining activities in the region. Many of the studies have concentrated on providing purely concentration data or concentration ratios, although more detailed uptake studies have been undertaken for freshwater mussels, turtles, and water lilies. The most-studied radionuclides are 238 U and 226 Ra. However, dose estimates based on current data highlight the importance of 210 Po, particularly for the natural (nonmining-related) dose. Data on uptake by terrestrial flora and fauna are scarce in comparison with aquatic organisms, and this knowledge gap will need to be addressed in relation to planning for uranium minesite rehabilitation.